2020
DOI: 10.1007/s00209-020-02491-y
|View full text |Cite|
|
Sign up to set email alerts
|

A note on Euler number of locally conformally Kähler manifolds

Abstract: Let M 2n be a compact Riemannian manifold of non-positive (resp. negative) sectional curvature. We call (M, J, θ) a d(bounded) locally conformally Kähler manifold if the lifted Lee formθ on the universal covering space of M is d(bounded). We shown that if M 2n is homeomorphic to a d(bounded) LCK manifold, then its Euler number satisfies the inequality (−1) n χ(M 2n ) ≥ (resp. >) 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One subclass consists of the so-called locally conformal Kähler manifolds, determined by a special property of the covariant derivative of J. Some of the recent investigations of locally conformal Kähler manifolds are made in [2,3,10,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…One subclass consists of the so-called locally conformal Kähler manifolds, determined by a special property of the covariant derivative of J. Some of the recent investigations of locally conformal Kähler manifolds are made in [2,3,10,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to attack Hopf Conjecture in the Kählerian case when K ≤ 0 by extending Gromov's idea, Cao-Xavier [5] and Jost-Zuo [16] independently introduced the concept of Kähler parabolicity, which includes nonpositively curved closed Kähler manifolds, and showed that their Euler characteristics have the desired property. In [12], the author proved the Hopf conjecture in some locally conformally Kähler manifolds case.…”
Section: Introductionmentioning
confidence: 99%
“…12. ([19, Theorem 9.3]) The operator Dε has a finite projective L 2 index give byL 2 Index Gε ( Dε ) = X L X ∧ exp( ε2π[ω]).…”
mentioning
confidence: 99%
“…In order to attack Hopf Conjecture in the Kählerian case when K ≤ 0 by extending Gromovs idea, Cao-Xavier [6] and Jost-Zuo [21] independently introduced the concept of Kähler non-ellipticity, which includes nonpositively curved compact Kähler manifolds, and showed that their Euler characteristics have the desired property. In [19], the author proved the Hopf conjecture in some locally conformally Kähler manifolds case.…”
Section: Introductionmentioning
confidence: 99%